The Contributions of Institutional Ethnography to Addressing Mental Health as a Public Health Crisis - Katerina Melino; Joanne Olson; Jude Spiers; Janet Rankin; Carla Hilario (International Journal of Qualitative Methods)
Mental illness represents a substantial global public health crisis, marked by high prevalence, significant economic costs, and profound impacts on individuals’ lives. Institutional ethnography (IE) is an approach to qualitative public health research that offers a methodologically rigorous way of addressing complex social problems. IE differs from many other qualitative research methods in its materialist, social ontology, which guides researchers to reveal and explicate the ruling relations that organize everyday life and which work against the interests of people at the standpoint location. Rather than focusing on populations, IE researchers focus on investigating processes and protocols that are activated locally through people’s everyday work and trace up into translocal ruling relations. The focus on social organization and empirically grounded analysis set IE apart from other qualitative methods and allow for different knowledge to be gained. IE is a methodology concerned with illuminating the voices of the marginalized and vulnerable and with increasing health equity by showing, as a first step, precisely how, when, and where systems are organized to benefit powerful institutional interests rather than people. The empirically grounded insights gained from IE research can inform the development of more equitable and responsive ways to run clinics that rely on the knowledge of those people who operate and use the services. They can also be used to develop policy frameworks that direct ongoing attention to the subjectivities of those whose work is implicated in planned health care reforms. We draw on our recent public health research to share our experiences of using IE methods and provide practical insights relating to each stage of the research process that may be valuable to novice researchers.